2020
DOI: 10.3390/insects11060333
|View full text |Cite
|
Sign up to set email alerts
|

Contact Effect Contribution to the High Efficiency of Lithium Chloride Against the Mite Parasite of the Honey Bee

Abstract: Lithium chemicals have been proven to be very effective in eradicating Varroa destructor, the detrimental parasite of the honey bee; however, little is known about the side effects on brood and long term consequences on the colony. Earlier, it was proposed that the action mechanisms of lithium chloride do not include the contact mode. Here, we investigate this question using a paper strip test to demonstrate the concentration-dependent effectiveness of lithium in the contact mode of action, confirming that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…The paper strip method of the application relies mainly on the contact effect of lithium. Although it was revealed that it can result in a significant mite drop, this efficacy could be achieved by an increased dose compared to that used via trickling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper strip method of the application relies mainly on the contact effect of lithium. Although it was revealed that it can result in a significant mite drop, this efficacy could be achieved by an increased dose compared to that used via trickling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no other varroacide agent is known to date to be applied by feeding with winter food, mainly because of the potential risk of accumulation in bees and their products. It has been shown that lithium chloride (LiCl) has a significant contact effect as well against the mites [ 32 ], and can be exerted at the colony level by using lithiated paper strips or trickling lithiated sucrose solution in pre-wintering broodless colonies [ 31 ]. In addition, lithium chloride applied via trickling outperformed the efficiency of common oxalic acid treatment and showed an elongated effectiveness [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ziegelmann et al [ 110 ] investigated its acaricidal impact by feeding honeybees and analysed their lifespan. This molecule, not yet on the market, showed efficient results against dispersal mites through oral and contact delivery methods [ 111 , 112 ]. However, the question arose about honeybee products potential contamination [ 113 ].…”
Section: Varroa Destructor Chemical and Semi-chemical Control Methodsmentioning
confidence: 99%
“…Raw sequences were first filtered for fragment length of a minimum of 50 base pairs and quality scores of ≥Q30 using Trimmomatic v.0.36 software [30] and were subsequently merged using Pear v.0.9.5 software [31]. Finally, sequences were clustered using Usearch v.11.0.667 software [32]. Each script was applied according to default settings.…”
Section: Bioinformatic Analysismentioning
confidence: 99%